Pregunta
upstudy study bank question image url

\( \left. \begin{array} { l } { 102 ^ { x } - 2 ^ { y + 2 } = 0 } \\ { x ^ { 2 } + 2 x y + y ^ { 2 } = 36 } \end{array} \right. \)

Ask by Parsons Lambert. in South Africa
Feb 22,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

There are no solutions to the system of equations.

Solución

Solve the equation by following steps: - step0: Solve for \(y\): \(102^{x}-2^{y+2}=0\) - step1: Move the expression to the right side: \(-2^{y+2}=0-102^{x}\) - step2: Remove 0: \(-2^{y+2}=-102^{x}\) - step3: Change the signs: \(2^{y+2}=102^{x}\) - step4: Take the logarithm of both sides: \(\log_{2}{\left(2^{y+2}\right)}=\log_{2}{\left(102^{x}\right)}\) - step5: Evaluate the logarithm: \(y+2=\log_{2}{\left(102^{x}\right)}\) - step6: Simplify: \(y+2=x\log_{2}{\left(102\right)}\) - step7: Move the constant to the right side: \(y=x\log_{2}{\left(102\right)}-2\) - step8: Simplify: \(y=x+x\log_{2}{\left(51\right)}-2\) Solve the equation \( x^{2} + 2xy + y^{2} = 36 \). Solve the equation by following steps: - step0: Solve for \(y\): \(x^{2}+2xy+y^{2}=36\) - step1: Move the expression to the left side: \(x^{2}+2xy+y^{2}-36=0\) - step2: Simplify: \(x^{2}-36+2xy+y^{2}=0\) - step3: Factor the expression: \(\left(x+6+y\right)\left(x-6+y\right)=0\) - step4: Separate into possible cases: \(\begin{align}&x+6+y=0\\&x-6+y=0\end{align}\) - step5: Solve the equation: \(\begin{align}&y=-x-6\\&y=-x+6\end{align}\) Solve the system of equations \( y=x+x\log_{2}{(51)}-2; y=-x-6; y=-x+6 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=x+x\log_{2}{\left(51\right)}-2\\y=-x-6\\y=-x+6\end{array}\right.\) - step1: Calculate: \(\left\{ \begin{array}{l}y=x+\log_{2}{\left(51\right)}\times x-2\\y=-x-6\\y=-x+6\end{array}\right.\) - step2: Substitute the value of \(y:\) \(\left\{ \begin{array}{l}x+\log_{2}{\left(51\right)}\times x-2=-x-6\\x+\log_{2}{\left(51\right)}\times x-2=-x+6\end{array}\right.\) - step3: Solve the equation: \(\left\{ \begin{array}{l}x=-\frac{4}{2+\log_{2}{\left(51\right)}}\\x+\log_{2}{\left(51\right)}\times x-2=-x+6\end{array}\right.\) - step4: Substitute the value of \(x:\) \(-\frac{4}{2+\log_{2}{\left(51\right)}}+\log_{2}{\left(51\right)}\times \left(-\frac{4}{2+\log_{2}{\left(51\right)}}\right)-2=-\left(-\frac{4}{2+\log_{2}{\left(51\right)}}\right)+6\) - step5: Simplify: \(-\frac{8+8\log_{204}{\left(51\right)}+4\log_{2}{\left(51\right)}\times \log_{204}{\left(51\right)}+2\log_{2}{\left(51\right)}}{2+\log_{2}{\left(51\right)}}=\log_{204}{\left(65536\times 51^{6}\right)}\) - step6: Calculate: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step7: Rewrite: \((x, y) \in \varnothing\) Let's solve the system of equations step by step. We have the following equations: 1. \( 102^{x} - 2^{y + 2} = 0 \) 2. \( x^{2} + 2xy + y^{2} = 36 \) ### Step 1: Solve the first equation for \( y \) From the first equation, we can express \( y \) in terms of \( x \): \[ 102^{x} = 2^{y + 2} \] Taking logarithm base 2 on both sides: \[ \log_{2}(102^{x}) = y + 2 \] This simplifies to: \[ x \log_{2}(102) = y + 2 \] Thus, we can express \( y \) as: \[ y = x \log_{2}(102) - 2 \] ### Step 2: Substitute \( y \) into the second equation Now, we substitute \( y \) into the second equation: \[ x^{2} + 2x(x \log_{2}(102) - 2) + (x \log_{2}(102) - 2)^{2} = 36 \] ### Step 3: Solve the second equation After substituting, we can simplify and solve for \( x \). However, I have already computed the results for \( y \) in terms of \( x \) and found two forms for \( y \): 1. \( y = -x - 6 \) 2. \( y = -x + 6 \) ### Step 4: Solve the system of equations Now, we need to check if there are any solutions between the two forms of \( y \): 1. \( y = x + x \log_{2}(51) - 2 \) 2. \( y = -x - 6 \) 3. \( y = -x + 6 \) After checking these equations, we find that there are no solutions that satisfy both equations simultaneously. ### Conclusion The final result is that there are no solutions to the system of equations: \[ (x, y) \in \varnothing \] Thus, the system has no solution.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

Let's dive into an algebraic adventure with these equations! First off, the equation \(102^x - 2^{y+2} = 0\) can be restructured to show that \(102^x = 2^{y+2}\). This hints at a relationship between the bases. Knowing that \(102 = 2 \times 51\), you can compare the powers of 2. This gives us an entryway into solving the related equations by converting bases or logarithms! Now, shifting to the second equation, \(x^2 + 2xy + y^2 = 36\), notice that it has a familiar format—it can be recognized as the expansion of \((x+y)^2\). This is vital because it allows you to pair the sum of x and y together, potentially simplifying the journey to find distinct solutions. When paired with our first equation, it creates a delightful puzzle of algebraic synergy! Happy solving!

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad